Wind-Induced Vibration Control of Dalian International Trade Mansion by Tuned Liquid Dampers. (8th September 2011) - Li, Hong-Nan; Yi, Ting-Hua; Jing, Qin-Yang; Huo, Lin-Sheng; Wang, Guo-Xin
Abstract : This paper focuses on the wind-induced vibration control of the Dalian international trade mansion (DITM) by using the tuned liquid dampers (TLDs). To avoid the intensive computationally demanding problem caused by tens of thousand of degrees of freedom (DOF) of the structure in the numerical analysis, the three-dimension finite element model of the DITM is first simplified to the equivalent series multi-DOF system. The wind loading is subsequently simulated by the Davenport model according to the structural environmental condition where the actual samples of wind speed are measured. Following that, the shallow- and deep-water wave theories are applied to model the liquid sloshing inside TLDs, the tank sizing, and required water depth, and numbers of TLDs are given according to the numerical results of different cases. Comparisons between uncontrolled and controlled displacement and acceleration responses of the DITM under wind forces show that the designed shallow tank has higher efficiency than the deep one, which can effectively reduce the structural response amplitudes and enhance the comfortableness of the mansion. The preliminary TLD design procedure presented in this paper could be applied as a reference to the analysis and design of the wind-induced vibration for high-rise buildings using the TLD.